Complement system activation in wild boar (Sus scrofa) following parenteral administration of heat-inactivated Mycobacterium bovis - Villar, Margarita; Rodríguez, Oscar; Vaz-Rodrigues, Rita; Pardo-Reyes, Angie E.; Rafael, Marta; Artigas-Jerónimo, Sara; de la Fuente, Gabriela; Fernández de Mera, Isabel G.; Juste, Ramón A.; Sevilla, Iker A.; Domínguez, Lucas; Gortázar, Christian; et al. (Frontiers in Veterinary Science, 2025)
IntroductionDevelopment of vaccines to preserve and improve human and animal health requires effective protective antigens, delivery platforms, and adjuvants. The immunostimulant based on heat-inactivated Mycobacterium bovis (IV) was developed to boost protective immune response in different animal species against pathogen infection and tick infestations.MethodsIn this study, a serum proteomics approach was used with functional annotations and enrichment network analysis for the characterization of immune pathways and biomarkers associated with parenteral administration of one, two, or three IV doses in the wild boar (Sus scrofa) animal model. An independent False Discovery Rate (FDR) analysis with the target-decoy approach provided by ProteinPilot™ was used, and positive identifications were considered when identified proteins reached a 1% FDR. Furthermore, pathogen surveillance was also performed to evaluate the IV treatment effect.ResultsThe proteomics analysis identified a total of 205 proteins, of which 97 displayed significant differential representation with 64 and 33 over (e.g., C4a, C5, C6, C7, and C9) and underrepresented (e.g., C3), respectively, in response to treatment. Results showed that IV administration activated both innate and adaptive immune responses through humoral immunity, regulation of the actin cytoskeleton pathway, coagulation cascade, and complement system. A single or two doses of IV significantly increased the activities of the classical, alternative, and lectin complement pathways. Moreover, a tendency was observed towards reducing seroprevalence in IV-treated wild boar over time for the causative agents of tuberculosis (Mycobacterium tuberculosis complex), pneumonia (Mycoplasma hyopneumoniae), and Aujeszky’s disease (porcine herpesvirus type 1).DiscussionThese results support a role for IV in stimulating immune and anti-inflammatory responses with possible application in different vaccine formulations for the control of infectious diseases.